Positive electrode material and preparation method and application thereof

By covering the zeolite imidazole ester skeleton structure material and the rigid conductive layer on the surface of the nickel-cobalt-manganese lithium ternary material, the problems of low gas adsorption efficiency and poor structural strength of the lithium battery positive electrode material are solved, and the comprehensive performance of the lithium battery is improved .

CN119297224APending Publication Date: 2025-01-10JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411312263.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art When processing gases generated by the lithium battery positive electrode material, the absorption efficiency is low and the adsorbent structural strength is poor, resulting in gas leakage and material breakage.

Method used

The surface of the nickel-cobalt lithium manganate ternary material is coated with zeolite imidazole ester skeleton structure material to form an adsorption layer, and the outer layer is coated with rigid conductive material to enhance structural stability and conductive ability.

Benefits of technology

It improves gas adsorption efficiency, enhances the conductivity of the positive electrode material, reduces the polarization of the battery, and improves the comprehensive performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297224A_ABST
    Figure CN119297224A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The positive electrode material of the present invention comprises: an inner core; the inner core is a nickel cobalt lithium manganate ternary material; the mass fraction of the nickel element in the nickel cobalt lithium manganate ternary material is greater than or equal to 80%; the adsorption layer is coated on the surface of the inner core; the adsorption layer is made of a zeolite imidazate framework structure material; the rigid conductive layer is coated on the surface of the adsorption layer; the material of the rigid conductive layer is selected from one or more of titanium carbide, tungsten carbide, zirconium nitride and titanium nitride. The surface of a nickel cobalt lithium manganate ternary material is coated with a zeolite imidazate framework structure material to form an adsorption layer, and gas generated by a positive electrode is directly adsorbed; and the outermost layer is coated with the rigid conductive material to form the rigid conductive layer, so that the structural stability of the zeolite imidazate skeleton structure material is enhanced, the zeolite imidazate skeleton structure material is not easy to break, and meanwhile, the conductivity of the positive electrode active material is enhanced by utilizing the high conductivity of the rigid conductive material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Currently, due to the use of high-nickel and high-voltage lithium batteries, positive electrode materials are more likely to generate oxygen. The oxidation reaction between oxygen and electrolyte produces a large amount of heat, affecting the safety performance of the battery. Therefore, how to deal with the gas derived from the positive electrode material has become one of the problems that need to be solved urgently. CN113764643A discloses a method based on MOF / COF porous skeleton materials to adsorb the gas generated by the positive electrode, and the adsorption materials such as MOF or COF are compositely coated on the surface of the positive electrode electrode to achieve the purpose of alleviating the oxygen release of the positive electrode. However, this coating method has the problem of low absorption efficiency, because the gas generated by the positive electrode directly comes from the surface of the positive electrode material, and the adsorbent coating on the surface of the electrode will cause part of the oxygen to leak from the surrounding of the electrode; CN113611856A discloses an adsorption layer on the surface of the positive electrode active material, and the adsorption layer is also a class of adsorbents such as MOF and COF wrapped on the surface of the active material. Although this method can directly and effectively absorb the oxygen released by the positive electrode material, generally MOF and COF materials have poor conductivity and need high-temperature carbonization to enhance the conductivity. However, the structural strength often deteriorates after high temperature and it is easy to break.

[0003] Therefore, how to efficiently and safely treat the gas originating from the positive electrode materials is still of great significance and there are still major challenges. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a positive electrode material and a preparation method and application thereof, wherein a zeolite imidazolate skeleton structure material is coated on the surface of a nickel cobalt lithium manganese oxide ternary material to form an adsorption layer to directly adsorb the gas generated from the positive electrode; and a rigid conductive material is coated on the outermost layer to form a rigid conductive layer to enhance the structural stability of the zeolite imidazolate skeleton structure material and make it not easy to break, and at the same time, the high conductivity of the rigid conductive material is used to enhance the conductivity of the positive electrode active material.

[0005] The first object of the present invention is to provide a positive electrode material, comprising:

[0006] Core; the core is a nickel-cobalt-lithium-manganese oxide ternary material; the mass fraction of nickel in the nickel-cobalt-lithium-manganese oxide ternary material is ≥80%;

[0007] An adsorption layer is coated on the surface of the inner core; the material of the adsorption layer is a zeolite imidazolate skeleton structure material;

[0008] A rigid conductive layer is coated on the surface of the adsorption layer; the material of the rigid conductive layer is selected from one or more of titanium carbide, tungsten carbide, zirconium nitride and titanium nitride.

[0009] In one embodiment of the present invention, the particle size of the core is 3 μm-15 μm;

[0010] And / or, the adsorption layer has a thickness of 0.1 μm-2 μm;

[0011] And / or, the rigid conductive layer has a thickness of 10 nm-100 nm.

[0012] In one embodiment of the present invention, the zeolite imidazolate framework material is selected from one or more of ZIF-67, ZIF-90 and ZIF-8.

[0013] A second object of the present invention is to provide a method for preparing a positive electrode material, comprising the following steps:

[0014] S1, dissolving a nickel-cobalt-lithium manganese oxide ternary material, a metal salt and an organic ligand in a solvent, and heating the solvent to obtain a nickel-cobalt-lithium manganese oxide ternary material having an adsorption layer coated on the surface;

[0015] S2. Immerse the nickel-cobalt-lithium manganese oxide ternary material with an adsorption layer on the surface described in S1 in a rigid conductive precursor solution, take it out, introduce reaction gas under a protective atmosphere, and calcine it to obtain the positive electrode material.

[0016] In one embodiment of the present invention, in S1, the metal salt is selected from cobalt salts and / or zinc salts; the cobalt salt is selected from cobalt nitrate and / or cobalt chloride; the zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc acetate, zinc iodide and zinc bromide;

[0017] and / or, the organic ligand is selected from 4,5-di(4-(piperidin-4-yl)phenyl)imidazole and / or 2-methylimidazole;

[0018] And / or, the solvent is selected from one or more of water, N,N-dimethylformamide, ethylene glycol and methanol.

[0019] In one embodiment of the present invention, in S1, the mass ratio of the nickel cobalt lithium manganese oxide ternary material, the metal salt and the organic ligand is (90-98):1:(3-6).

[0020] In one embodiment of the present invention, in S1, the heating reaction is carried out at a temperature of 100°C-200°C and for a time of 1h-6h.

[0021] In one embodiment of the present invention, in S2, the rigid conductive precursor in the rigid conductive precursor solution is selected from one or more of titanium tetrachloride, tungsten tetrachloride and zirconium tetrachloride;

[0022] and / or, the concentration of the rigid conductive precursor solution is 0.01 mol / L-0.5 mol / L;

[0023] And / or, the reaction gas is selected from one or more of methane, ethane, n-butane and ammonia.

[0024] In one embodiment of the present invention, in S2, the soaking time is 0.5h-2h;

[0025] And / or, the protective atmosphere is selected from nitrogen, argon or helium;

[0026] And / or, the calcination temperature is 800°C-1400°C, and the calcination time is 2h-6h.

[0027] The third object of the present invention is to provide a lithium ion battery, comprising the positive electrode material or the positive electrode material prepared by the method described.

[0028] The technical solution of the present invention has the following advantages over the prior art:

[0029] The present invention coats the surface of the nickel-cobalt-lithium manganese oxide ternary material with a zeolite imidazolate skeleton structure material to form an adsorption layer, which directly adsorbs the gas generated from the positive electrode and improves efficiency; and coats the outermost layer with a rigid conductive material to form a rigid conductive layer, which enhances the structural stability of the zeolite imidazolate skeleton structure material and makes it difficult to break. At the same time, the high conductivity of the rigid conductive material is used to enhance the conductivity of the positive electrode active material, reduce the polarization of the battery, and improve the comprehensive performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0031] Figure 1 This is a schematic diagram of the structure of the positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0032] As described in the background technology, the current positive electrode active materials, especially high nickel ternary materials, are prone to produce harmful gases in ternary batteries due to the increase in nickel content, affecting the performance and safety of lithium batteries. The current conventional method is to add adsorption materials such as ZIF and MOF materials to the slurry to form the body of the pole piece to adsorb the gas generated by the positive active materials. However, this method of directly introducing adsorption materials also brings new problems. On the one hand, due to the poor structural strength of ZIF and MOF materials, they are easily broken by rolling; on the other hand, such ZIF and MOF materials are generally present in the form of particles in the homogenization formula. Since they are not in full contact with the positive electrode active material, the gas adsorption efficiency will be greatly reduced, which not only affects the gas adsorption, but also increases the contact internal resistance of the battery.

[0033] In order to solve the above technical problems, the present invention provides a positive electrode material and a preparation method and application thereof, wherein a zeolite imidazolate skeleton structure material is coated on the surface of a nickel cobalt lithium manganese oxide ternary material to form an adsorption layer, which directly adsorbs the gas generated from the positive electrode to improve efficiency; and a rigid conductive material is coated on the outermost layer to form a rigid conductive layer, thereby enhancing the structural stability of the zeolite imidazolate skeleton structure material and making it less likely to break. At the same time, the high conductivity of the rigid conductive material is used to enhance the conductivity of the positive electrode active material, reduce the polarization of the battery, and improve the comprehensive performance of the lithium battery.

[0034] The first object of the present invention is to provide a positive electrode material, comprising:

[0035] Core; the core is a nickel-cobalt-lithium-manganese oxide ternary material; the mass fraction of nickel in the nickel-cobalt-lithium-manganese oxide ternary material is ≥80%;

[0036] An adsorption layer is coated on the surface of the inner core; the material of the adsorption layer is a zeolite imidazolate skeleton structure material;

[0037] A rigid conductive layer is coated on the surface of the adsorption layer; the material of the rigid conductive layer is selected from one or more of titanium carbide, tungsten carbide, zirconium nitride and titanium nitride.

[0038] In one embodiment of the present invention, the particle size of the core is 3 μm-15 μm;

[0039] And / or, the adsorption layer has a thickness of 0.1 μm-2 μm;

[0040] And / or, the thickness of the adsorption layer is proportional to the mass fraction of the nickel element in the nickel-cobalt-lithium-manganese oxide ternary material. The higher the content of the nickel element, the greater the gas production. Therefore, the thickness of the adsorption layer is required to be higher to meet the demand of absorbing more gas;

[0041] And / or, the rigid conductive layer has a thickness of 10 nm-100 nm.

[0042] In one embodiment of the present invention, the zeolite imidazolate framework material is selected from one or more of ZIF-67, ZIF-90 and ZIF-8.

[0043] A second object of the present invention is to provide a method for preparing a positive electrode material, comprising the following steps:

[0044] S1, dissolving a nickel-cobalt-lithium manganese oxide ternary material, a metal salt and an organic ligand in a solvent, and heating the solvent to obtain a nickel-cobalt-lithium manganese oxide ternary material having an adsorption layer coated on the surface;

[0045] S2. Immerse the nickel-cobalt-lithium manganese oxide ternary material with an adsorption layer on the surface described in S1 in a rigid conductive precursor solution, take it out, introduce reaction gas under a protective atmosphere, and calcine it to obtain the positive electrode material.

[0046] In one embodiment of the present invention, in S1, the metal salt is selected from cobalt salts and / or zinc salts; the cobalt salt is selected from cobalt nitrate and / or cobalt chloride; the zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc acetate, zinc iodide and zinc bromide;

[0047] and / or, the organic ligand is selected from 4,5-di(4-(piperidin-4-yl)phenyl)imidazole and / or 2-methylimidazole;

[0048] And / or, the solvent is selected from one or more of water, N,N-dimethylformamide, ethylene glycol and methanol.

[0049] In one embodiment of the present invention, in S1, the mass ratio of the nickel cobalt lithium manganese oxide ternary material, the metal salt and the organic ligand is (90-98):1:(3-6).

[0050] In one embodiment of the present invention, in S1, the heating reaction is carried out at a temperature of 100°C-200°C and for a time of 1h-6h.

[0051] In one embodiment of the present invention, in S2, the rigid conductive precursor in the rigid conductive precursor solution is selected from one or more of titanium tetrachloride, tungsten tetrachloride and zirconium tetrachloride;

[0052] and / or, the concentration of the rigid conductive precursor solution is 0.01 mol / L-0.5 mol / L;

[0053] And / or, the reaction gas is selected from one or more of methane, ethane, n-butane and ammonia.

[0054] In one embodiment of the present invention, in S2, the soaking time is 0.5h-2h;

[0055] And / or, the protective atmosphere is selected from nitrogen, argon or helium;

[0056] And / or, the calcination temperature is 800°C-1400°C, and the calcination time is 2h-6h.

[0057] The third object of the present invention is to provide a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the active material of the positive electrode sheet is the positive electrode material.

[0058] In one embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material, a conductive agent, and a binder. The preparation of the negative electrode sheet can be carried out by conventional methods in the art, wherein an illustrative preparation method is: preparing an electrode slurry of a negative electrode active material, a binder, and a conductive agent in a certain proportion, and then coating it on at least one surface of the negative electrode current collector, and after drying and pressing, a negative electrode sheet is obtained.

[0059] The type of the negative electrode current collector is not specifically limited and can be selected according to actual needs. In some embodiments, the negative electrode current collector can be copper foil, carbon-coated copper foil or polymer conductive film.

[0060] The type and content of the negative electrode active material are not specifically limited and can be selected according to actual needs. In some embodiments, the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon, silicon oxide, tin, lithium titanate, etc.

[0061] The type and content of the above conductive agent are not specifically limited and can be selected according to actual needs. In some embodiments, the above conductive agent includes one or more of conductive carbon black, carbon nanotubes, acetylene black, graphene, Ketjen black, carbon nanofibers, etc. It should be understood that without violating the spirit of the present application, other conductive agents that can achieve the functions of the present application can be selected according to specific needs without being limited thereto.

[0062] The type and content of the above-mentioned binder are not specifically limited and can be selected according to actual needs. In some embodiments, the above-mentioned binder includes one or more of polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, sodium carboxymethyl cellulose, polymethacrylamide, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyamide, polyimide, polyacrylate, styrene-butadiene rubber, sodium alginate, chitosan, polyethylene glycol, guar gum, etc.

[0063] In one embodiment of the present invention, the preparation method of the positive electrode sheet is the same as that of the negative electrode sheet, which is to prepare the positive electrode active material, binder and conductive agent into electrode slurry in a certain proportion, and then apply it on at least one surface of the positive electrode collector, and then obtain it after drying and pressing.

[0064] The type of the positive electrode current collector is not specifically limited and can be selected according to actual needs. For example, the positive electrode current collector can be aluminum foil, nickel foil or a polymer conductive film. The types of the conductive agent and the binder in the positive electrode sheet refer to the negative electrode sheet, and the present invention will not repeat them.

[0065] In one embodiment of the present invention, the electrolyte includes one or more of an organic liquid electrolyte, an organic solid electrolyte, a solid ceramic electrolyte, a gel electrolyte, etc. Preferably, the electrolyte is an organic liquid electrolyte, which is obtained by dissolving a lithium salt in a non-aqueous organic solvent; wherein the lithium salt includes one or more of lithium difluorophosphate, lithium hexafluorophosphate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate and lithium difluorooxalate borate. The non-aqueous organic solvent may include one or more of cyclic carbonates, chain carbonates, and carboxylates. wherein the cyclic carbonate may be selected from one or more of ethylene carbonate, propylene carbonate, butylene carbonate, and γ-butyrolactone; the chain carbonate may be selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl acetate, ethyl acetate, ethyl propionate, etc.

[0066] In one embodiment of the present invention, the isolation membrane is polyethylene, polypropylene, polyvinylidene fluoride or non-woven fabric, and their multilayer composite membranes and modified membranes such as ceramic modification and PVDF modification of the above-mentioned membranes can be selected according to actual needs.

[0067] It should be understood that the preparation methods of the positive electrode sheet, negative electrode sheet, separator and electrolyte in the present application can select other preparation methods that can achieve the functions of the present application according to specific needs without violating the spirit of the present application, without being limited thereto. In one embodiment of the method for manufacturing a lithium-ion battery, the preparation method includes: winding, folding or stacking the above-mentioned negative electrode sheet, separator and positive electrode sheet in sequence into an electrode assembly, placing the electrode assembly in, for example, an aluminum-plastic film, and injecting an electrolyte, followed by vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.

[0068] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0069] In the present invention, unless otherwise specified, the nickel-cobalt-lithium-manganese-oxide ternary material used in the embodiments and comparative examples of the present invention is purchased from Soaring Eagle Technology; the nickel-cobalt-lithium-manganese-oxide ternary material is ground into granular materials with a particle size of about 10 μm before use.

[0070] Example 1

[0071] Reference Figure 1As shown, the positive electrode material and the preparation method thereof of this embodiment specifically include the following steps:

[0072] S1. Nickel cobalt lithium manganese oxide ternary material (nickel element mass fraction of 80%), cobalt nitrate hexahydrate and 2-methylimidazole were uniformly dissolved in water at a mass ratio of 95:1:4 to prepare a mixed solution with a total concentration of 20 g / L, and the mixture was slowly heated to 150°C and stirred for 4 hours to deposit a 1 μm thick ZIF precursor coating on the surface of the nickel cobalt lithium manganese oxide ternary material;

[0073] S2. The prepared material is washed with water, re-put into a 0.2 mol / L titanium tetrachloride solution, stirred and soaked for 1 hour, then the positive electrode material after soaking is taken out, methane gas is introduced under N2 atmosphere, and calcined at 1000°C for 4 hours to obtain a positive electrode material, namely NCM@ZIF@TiC, in which the thickness of the TiC layer is 50 nm.

[0074] Example 2

[0075] The method is basically the same as Example 1, except that the mass fraction of the nickel element in the nickel-cobalt-lithium manganese oxide ternary material is 85%, and specifically includes the following steps:

[0076] S1. Nickel cobalt lithium manganese oxide ternary material (nickel element mass fraction of 85%), cobalt nitrate hexahydrate and 2-methylimidazole are uniformly dissolved in water at a mass ratio of 95:1:4 to prepare a mixed solution with a total concentration of 20 g / L, and the mixture is slowly heated to 150°C and stirred for reaction for 4 hours. The above is repeated once, and a 2 μm thick ZIF precursor coating is deposited on the surface of the nickel cobalt lithium manganese oxide ternary material;

[0077] S2. The prepared material is washed with water, re-put into a 0.2 mol / L titanium tetrachloride solution, stirred and soaked for 1 hour, then the positive electrode material after soaking is taken out, methane gas is introduced under N2 atmosphere, and calcined at 1000°C for 4 hours to obtain a positive electrode material, namely NCM@ZIF@TiC, in which the thickness of the TiC layer is 50 nm.

[0078] Example 3

[0079] The method is basically the same as Example 1, except that the mass ratio of the nickel cobalt lithium manganese oxide ternary material, cobalt nitrate hexahydrate and 2-methylimidazole is 90:1:4, and specifically includes the following steps:

[0080] S1. Nickel cobalt lithium manganese oxide ternary material (nickel element mass fraction is 80%), cobalt nitrate hexahydrate and 2-methylimidazole are uniformly dissolved in water at a mass ratio of 90:1:4 to prepare a mixed solution with a total concentration of 20 g / L, and the mixture is slowly heated to 150°C and stirred for 4 hours to deposit a 2 μm thick ZIF precursor coating on the surface of the nickel cobalt lithium manganese oxide ternary material;

[0081] S2. The prepared material is washed with water, re-put into a 0.2 mol / L titanium tetrachloride solution, stirred and soaked for 1 hour, then the positive electrode material after soaking is taken out, methane gas is introduced under N2 atmosphere, and calcined at 1000°C for 4 hours to obtain a positive electrode material, namely NCM@ZIF@TiC, in which the thickness of the TiC layer is 50 nm.

[0082] Example 4

[0083] The method is basically the same as Example 1, except that the calcination reaction temperature is 1400° C., and specifically includes the following steps:

[0084] S1. Nickel cobalt lithium manganese oxide ternary material (nickel element mass fraction of 80%), cobalt nitrate hexahydrate and 2-methylimidazole were uniformly dissolved in water at a mass ratio of 95:1:4 to prepare a mixed solution with a total concentration of 20 g / L, and the mixture was slowly heated to 150°C and stirred for 4 hours to deposit a 1 μm thick ZIF precursor coating on the surface of the nickel cobalt lithium manganese oxide ternary material;

[0085] S2. The prepared material is washed with water, re-put into a 0.2 mol / L titanium tetrachloride solution, stirred and soaked for 1 hour, then the positive electrode material after soaking is taken out, methane gas is introduced under a N2 atmosphere, and calcined at 1400°C for 4 hours to obtain a positive electrode material, namely NCM@ZIF@TiC, in which the thickness of the TiC layer is 50 nm.

[0086] Comparative Example 1

[0087] The method is basically the same as Example 1, except that the rigid conductive layer is not prepared, and specifically includes the following steps:

[0088] The nickel-cobalt-lithium manganese oxide ternary material, cobalt nitrate hexahydrate and 2-methylimidazole were uniformly dissolved in water in a mass ratio of 95:1:4 to prepare a mixed solution with a total concentration of 20 g / L. The temperature was slowly raised to 150°C and stirred for reaction for 4 hours. A 1 μm thick ZIF precursor coating was deposited on the surface of the nickel-cobalt-lithium manganese oxide ternary material. The cathode material, namely NCM@ZIF, was obtained by calcining the solution at 1000°C for 4 hours under an argon atmosphere.

[0089] Comparative Example 2

[0090] The method is basically the same as Example 1, except that the mass ratio of the nickel cobalt lithium manganese oxide ternary material, cobalt nitrate hexahydrate and 2-methylimidazole is 100:1:4.

[0091] Comparative Example 3

[0092] The process is basically the same as Example 1, except that the calcination reaction temperature is 600°C.

[0093] Comparative Example 4

[0094] Nickel cobalt lithium manganese oxide ternary material.

[0095] Performance Test 1

[0096] The positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested for specific surface area, compaction density, etc.:

[0097] (1) Specific surface area: The sample is placed in a BET tester and nitrogen (N2) is introduced. The specific surface area is measured by the N2 adsorption method. The specific surface area of ​​the material is characterized by the amount of gas adsorption. That is, after nitrogen is introduced for a period of time, the specific surface area of ​​the composite material is represented by the amount of gas adsorption collected together.

[0098] (2) Maximum compaction density: Because the rigid conductive layer can stabilize the structural stability of the adsorption layer, the maximum pressure that the positive electrode can withstand without breaking the structure during the rolling process of the positive electrode sheet is increased by increasing the compaction density. The standard test method is to test the maximum pressure that the electrode sheet can withstand at different compaction densities (3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 ) and compacted, and the SEM and CP of the cross section were used to determine whether the adsorption layer material was broken;

[0099] (3) Conductivity: The conductivity is measured by powder level resistivity test. A certain amount of cathode material is placed in the test container of the powder resistance meter. The cathode material of the same mass is pressed into a dense block under a pressure of 5T, and its resistivity is tested in this state.

[0100] Table 1 shows the results of physical and chemical tests:

[0101] Table 1

[0102] Sample <![CDATA[Specific surface area m 2 / g]]> <![CDATA[Maximum compaction density g / cm 3 > Conductivity s / cm Example 1 1180 3.50 1.2 Example 2 1320 3.45 1.18 Example 3 1300 3.45 1.17 Example 4 1170 3.51 1.22 Comparative Example 1 1220 3.3 0.7 Comparative Example 2 1175 3.50 1.22 Comparative Example 3 1180 3.4 1.1 Comparative Example 4 900 3.55 0.6

[0103] As can be seen from Table 1, the results of the specific surface area show that NCM@ZIF@TiC and NCM@ZIF have similar specific surface areas, indicating that the deposition of TiC will not significantly reduce its specific surface area, and the active sites will not be reduced; and from the maximum compaction density of the powder, it can be seen that a layer of TiC is deposited on ZIF, and the high mechanical strength of TiC significantly increases its compaction density without material breakage; and the conductive performance is improved by about 50% compared with NCM@ZIF; through the analysis of the embodiments and comparative examples, it can be obtained that with the increase of the thickness of the adsorption layer, the specific surface area also increases, but at the same time it also brings a slight decrease in the compaction density; lowering the high-temperature titanization temperature, the maximum compaction density decreases, the reason is that the titanization temperature determines the strength of the rigid layer, so after lowering the temperature, the rigidity of the adsorption layer structure decreases; and through the comparison of Example 1 and Comparative Example 1, Example 1 with a rigid conductive layer shows a larger compaction density, stronger conductivity, and a more stable structure; and all groups are better than the single nickel cobalt manganese lithium ternary material of Comparative Example 4.

[0104] Performance Test 2

[0105] Battery Assembly:

[0106] Negative electrode sheet: The negative electrode active material is graphite and silicon oxide (mass ratio 8:2), the conductive agent is conductive carbon black (SP), the binder is polyacrylic acid (PAA) and styrene-butadiene rubber (SBR) (mass ratio 2:1), and the negative electrode current collector is 6μm copper foil; the negative electrode active material, conductive agent and binder are mixed according to the mass ratio of 95.5:1.5:3, and deionized water is added and stirred to form a uniform and stable negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode current collector, and the coating surface density is 105g / m 2 After drying, the negative electrode sheet is obtained, and the compaction density is 1.5g / cm 3 .

[0107] Positive electrode sheet: The positive electrode active materials are the positive electrode active materials prepared in Examples 1-4 and Comparative Examples 1-4, respectively; the conductive agents are conductive carbon black (SP) and carbon nanotubes (mass ratio 2:1); the binder is PVDF5130; and the positive electrode current collector is 13 μm aluminum foil; the positive electrode active material, the conductive agent and the binder are mixed in a mass ratio of 97:2:1, and NMP is added and stirred to form a uniformly mixed and stable positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the coating surface density is 195 g / m 2 After drying and cold pressing, the positive electrode sheet is obtained, and the compaction density is 3.4g / cm 3 .

[0108] Isolation film: The base film of the isolation film is a polypropylene film with a thickness of 9+3+3+3μm.

[0109] Electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1, and then fully dried LiPF6 is dissolved in a mixed organic solvent at a ratio of 1.2 mol / L, and vinylene carbonate is added to prepare an electrolyte.

[0110] Assembly of lithium-ion battery: arrange the positive electrode plate, separator, negative electrode plate and separator in order, and wind them to obtain a battery cell; ultrasonically weld the pole ears, seal the top and side of the aluminum-plastic film, dry to remove moisture, inject electrolyte and then seal again, inject electrolyte into the dry battery cell, soak for 24 hours, and then form at 45°C. The formation process: charge at 0.05C to 3.4V, and then charge at 0.2C to 3.75V; after aging at room temperature for 24 hours, the lithium-ion battery is completed.

[0111] Performance Test:

[0112] The assembled lithium-ion battery is tested for internal resistance, cycle performance, etc.:

[0113] (1) Internal resistance: The battery was charged to 4.25V at 0.5C constant current and to 0.05C at 4.25V constant voltage according to the standard test process; left to stand for 30 minutes; discharged at 1C current for 30 minutes to 50% SOC, and the DC internal resistance of the battery was tested using a DC internal resistance meter;

[0114] (2) Rate retention rate: The battery is charged to 4.25V at 0.5C constant current according to the standard test process, and then charged to 0.05C at 4.25V constant voltage; let it stand for 30 minutes; discharge to the lower limit voltage of 2.5V at 1C current; let it stand for 30 minutes; then repeat the above steps in sequence, and discharge at 1C, 2C, 3C, and 5C currents. The 5C rate retention rate = 5C discharge capacity / 1C standard discharge capacity;

[0115] (3) 1C cycle: 1. Charge the battery to 4.25V at 0.5C constant current according to the standard test process, and then charge it to 0.05C at 4.25V constant voltage; 2. Let it stand for 30 minutes; 3. Discharge it to the lower limit voltage of 2.5V at 1C current; 4. Let it stand for 30 minutes, and repeat the above cycle steps until the discharge capacity of the battery is less than 80% of the initial capacity and stop the test;

[0116] (4) 1C energy density: The battery is charged to 4.25V at 0.5C constant current according to the standard test process, and then charged to 0.05C at 4.25V constant voltage; left to stand for 30 minutes; discharged to the lower limit voltage of 2.5V at 1C current; left to stand for 30 minutes, then 1C energy density = 1C discharge capacity * 1C discharge average voltage / total weight of the battery;

[0117] (5) Gas volume test: The gas volume test is conducted by the water displacement method and measured using a volume tester. Based on the initial weight m1 of the battery and the mass m2 immersed in water, the buoyancy of the battery in water = ρgV, which is proportional to the weight. The density ρ of water and the mass acceleration g are known, so the volume V = (m1-m2) / ρg;

[0118] (6) Hot box test: The battery is charged to 4.25V at 0.5C constant current according to the national standard (GB / T 31485-2015) test process, and then charged to 0.05C at 4.25V constant voltage; the battery is fully charged and placed in a hot box, and the temperature is raised to 130℃ at a rate of 5℃ / min and kept for half an hour. After observing for half an hour, if there is no fire or smoke, the temperature is continued to be raised at a rate of 5℃ / min, and the failure temperature is tested in sequence every 5℃ until the battery fails. The temperature at this time is the failure temperature;

[0119] Table 2 shows the electrochemical performance test results:

[0120] Table 2

[0121]

[0122] As can be seen from Table 2, the batteries of Examples 1-4 all have good comprehensive electrochemical properties. In Example 2, since the nickel-cobalt-lithium manganese oxide ternary material has a higher nickel core, the gas production volume is slightly increased, the safety is slightly reduced, and the hot box temperature is slightly reduced; in Example 3, the ZIF coating ratio is increased. As the proportion of ZIF material increases, the compaction density of the pole piece is slightly reduced, and the proportion of active substances in the same volume is reduced, so the energy density is slightly reduced, but the presence of more ZIF can absorb more gases generated by the lithium battery, so the safety hot box test temperature is slightly increased; in Example 4, since the titaniumization temperature of the rigid layer is increased, its structure is more stable, thereby improving the stability of the coating layer, and the energy density, gas adsorption, safety performance, etc. are all slightly improved; in Comparative Example 1, due to the increase of the titaniumization temperature of the rigid layer, the structure is more stable, thereby improving the stability of the coating layer, and the energy density, gas adsorption, safety performance, etc. are all slightly improved. By eliminating the rigid coating, the ZIF material is easy to break, so its compaction density is greatly reduced, resulting in a significant reduction in the energy density of the battery, and the gas adsorption efficiency is reduced due to the breakage of the material, affecting the safety performance; Comparative Example 2 reduces the amount of the ZIF coating layer. Due to the reduction of the ZIF material, the gas adsorption amount is reduced, so the harmful gas inside the battery increases, the polarization inside the battery is increased, and the electrochemical performance of the battery is deteriorated; Comparative Example 3 reduces the titaniumization temperature of the rigid coating, which affects the structural strength of the rigid layer, making the battery easy to break, reducing the gas adsorption efficiency and affecting the safety performance; Comparative Example 4 simultaneously eliminates the adsorption layer and the rigid conductive layer, resulting in a significant increase in the volume of gas inside the battery, and the battery polarization phenomenon is seriously deteriorated, so the comprehensive electrochemical performance of the battery is the worst.

[0123] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A positive electrode material, characterized in that include: kernel; The core is a ternary material of nickel-cobalt-lithium manganese oxide; The mass fraction of nickel in the nickel-cobalt-lithium manganese oxide ternary material is ≥80%; An adsorption layer is coated on the surface of the inner core; the material of the adsorption layer is a zeolite imidazolate skeleton structure material; A rigid conductive layer is coated on the surface of the adsorption layer; the material of the rigid conductive layer is selected from one or more of titanium carbide, tungsten carbide, zirconium nitride and titanium nitride.

2. The positive electrode material according to claim 1, characterized in that The particle size of the core is 3 μm-15 μm; And / or, the adsorption layer has a thickness of 0.1 μm-2 μm; And / or, the rigid conductive layer has a thickness of 10 nm-100 nm.

3. The positive electrode material according to claim 1, characterized in that The zeolite imidazolate framework material is selected from one or more of ZIF-67, ZIF-90 and ZIF-8.

4. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1, dissolving a nickel-cobalt-lithium manganate ternary material, a metal salt, and an organic ligand in a solvent, and heating the resulting solution to obtain a nickel-cobalt-lithium manganate ternary material having an adsorption layer coated on its surface; S2. Immerse the nickel-cobalt-manganese oxide lithium ternary material with an adsorption layer on its surface as described in S1 in a rigid conductive precursor solution, take it out, introduce reaction gas under a protective atmosphere, and calcine it to obtain the positive electrode material.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: In S1, the metal salt is selected from cobalt salts and / or zinc salts; the cobalt salt is selected from cobalt nitrate and / or cobalt chloride; the zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc acetate, zinc iodide and zinc bromide; and / or, the organic ligand is selected from 4,5-bis(4-(piperidin-4-yl)phenyl)imidazole and / or 2-methylimidazole; And / or, the solvent is selected from one or more of water, N,N-dimethylformamide, ethylene glycol and methanol.

6. The method for preparing the positive electrode material according to claim 4, wherein: In S1, the mass ratio of the lithium nickel cobalt manganese oxide ternary material, the metal salt and the organic ligand is (90-98):1:(3-6).

7. The method for preparing the positive electrode material according to claim 4, wherein: In S1, the heating reaction temperature is 100°C-200°C, and the time is 1h-6h.

8. The method for preparing the positive electrode material according to claim 4, wherein: In S2, the rigid conductive precursor in the rigid conductive precursor solution is selected from one or more of titanium tetrachloride, tungsten tetrachloride and zirconium tetrachloride; and / or, the concentration of the rigid conductive precursor solution is 0.01 mol / L-0.5 mol / L; And / or, the reaction gas is selected from one or more of methane, ethane, n-butane and ammonia.

9. The method for preparing the positive electrode material according to claim 4, wherein: In S2, the soaking time is 0.5h-2h; And / or, the protective atmosphere is selected from nitrogen, argon or helium; And / or, the calcination temperature is 800° C.-1400° C., and the calcination time is 2 h-6 h.

10. A lithium-ion battery, characterized in that: The method comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN113611856A

  • Electrode plate and lithium ion battery

    CN113764643A